Tectonic setting of the Ohre/Eger Graben between the central part of the Ceske stredohori Mts. and the Most Basin, a regional study - Cajz,V.; Valecka,J. (Journal of Geosciences, 2010)
The paper presents the results of a new detailed survey in the SW part of the Ceske stredohori Mts. (a section of the Ohre/Eger Graben/Rift), focused on its tectonic setting. Courses of the SE marginal graben faults are traced in detail. This limiting fault zone is described as a horst, with the graben fill being structured into rhomboidal blocks; older known faults are specified, and new faults are depicted. Respecting the age ranges of the preserved stratigraphic units, fault movements are classified into those older than 36 Ma, younger than 24 Ma and younger than 16 Ma (with a possible age younger than 9 Ma), based on different lithologies and abrupt lithological changes (i.e., the rock boundaries). The faults are compared with the earlier-defined paleostress fields. Fault reversals were detected on several faults. An important role of crystalline basement ridges during the graben formation was identified: three complex tectonic structures are spatially associated with these ridges. Two areas with distinct tectonic and geological development were defined within the Ohre/Eger Graben. The Saxothuringian - Tepla-Barrandian terrane boundary was found to be less important for graben formation during the Cenozoic. This disagrees with simplified riftogenic model of the Ohre/Eger Graben. The supposed ”Litomerice Deep-seated Fault“, possibly representing a first-order terrane boundary, cold not be confirmed in the post-Paleozoic rocks - this structure did not function as a fault during Cenozoic times.
Keywords: surface-detected faults; timing of tectonic activity; Ohre/Eger Graben/Rift; Bohemian Cretaceous Basin; Ceske stredohori Volcanic Complex; Most Basin; Cenozoic